Contrast enhancement for colour images based on discrete wavelet transform - Mohd Zaidi, Noor Afina (2017)
Low contrast images demanded contrast enhancement algorithm to intensify the visual outcomes by displaying more details. The image is facing trouble from poor contrast and scarcity of information since the image intelligibility simply affected by a diverse environment situation or quality level of photography equipment used. However, the contrast enhancement algorithm normally challenging to fulfil the desired results so the image processing is executed manually for each specified images. This report recommended the image enhancement scheme using DWT implement to the Saturation components with the decomposed approximation coefficients modify by a derived mapping function of scale-up triangle transform while the Luminance component can enhance by using the CLAHE. This enhancement algorithm demands the vice versa conversion between the RGB and HSV colour space where modification of specification desired can achieve in HSV colour space. The qualitative and quantitative performance evaluation can be recognized by using the subjective of visual quality display assessment and objective parameters by AMBE, MSE and PSNR. Therefore, the performance evaluation received can prove that the improvement result of the algorithm implemented by MATLAB can be accomplished.